2018
DOI: 10.1155/2018/3239785
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Application of an UHPLC‐MS/MS Method for Comparative Pharmacokinetic Study of Eight Major Bioactive Components from Yin Chen Hao Tang in Normal and Acute Liver Injured Rats

Abstract: Yin Chen Hao Tang (YCHT) is one of the most famous hepatoprotective herbal formulas in China, but its pharmacokinetic investigation in model rats has been rarely conducted. In this study, the hepatic injury model was caused by intraperitoneal injections of carbon tetrachloride (CCl4), and YCHT was orally administered to the model and normal rats. An ultrahigh performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method was established to analyze the plasma pharmacokinetics of eight major bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another study of oral administration at a dose of 50 mg/kg resulted in the C max value of 0.4 µg/L within 14 min. However, treatment with a decoction prepared from 720 g of A. capillaris resulted in a relatively low plasma concentration of only 3.5 µg/L after feeding [61]. Similarly, administration of Radix angelicae pubescentis extract containing 0.055 mg/kg scopoletin did not result in detectable levels of the compound in rat plasma [72].…”
Section: Scopoletinmentioning
confidence: 90%
See 1 more Smart Citation
“…Another study of oral administration at a dose of 50 mg/kg resulted in the C max value of 0.4 µg/L within 14 min. However, treatment with a decoction prepared from 720 g of A. capillaris resulted in a relatively low plasma concentration of only 3.5 µg/L after feeding [61]. Similarly, administration of Radix angelicae pubescentis extract containing 0.055 mg/kg scopoletin did not result in detectable levels of the compound in rat plasma [72].…”
Section: Scopoletinmentioning
confidence: 90%
“…Analysis of pharmacokinetic parameters of scoparone could achieve a wide range of the C max values from 0.02 mg/L or up to 16.1 mg/L accompanying with standard compounds as Yin-Chen-Hao-Tang ingredients, and most T max values ranged from 6 to 54 min with the exception of one study that reported a T max value of 1.9 h after combined administration with Gardenia jasminoides Ellis [59]; the corresponding elimination half-life ranges from 25.8 min to 5.11 h [11,[59][60][61][62][63]. The IC 50 value for scoparone-associated significant inhibition of the proliferation of DU145 prostate cancer cells is 8.5 mg/L (41.3 µmol/L) [64].…”
Section: Scoparonementioning
confidence: 99%
“…The aforementioned results suggest that scopoletin undergoes extensive metabolism in the body. Wang et al determined that hepatic injury does not significantly influence the pharmacokinetics of scopoletin (Wang et al, 2018). The reason for this may be that cytochrome P450 enzymes had underwent partial change in the process of liver injury.…”
Section: Absorption Metabolism and Eliminationmentioning
confidence: 99%
“…Moreover, oral administration of YCHT in the acute liver injury model rat group and the normal rat group showed significant differences in the pharmacokinetic parameters of geniposide. Compared with the normal rat group, the Cmax and AUC0-∞ value of geniposide in the model group was higher, indicating that the geniposide significantly accumulated in the body under the disease state of liver injury [ 100 ]. The pharmacokinetics of geniposide in a compound Huanglianzhizi decoction or a Huanglianjiedu decoction in middle cerebral artery occlusion (MCAO) model rat analysis showed that compared with the control group, the AUC and Cmax of the two compound treatment groups showed a significant increase trend.…”
Section: Pharmacokinetic Study Of Geniposidementioning
confidence: 99%